PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP MINAT BELI KONSUMEN PRODUK PRIVATE LABEL PADA SUPER INDO SUPERMARKET CABANG KELAPA DUA - Salma Zahra Alharits; Agus Wahyono (Jurnal Manajemen, 2022)
This study aims to determine the effect of Product Quality, Price, amd Brand Equity on customers’ Purchase Interest of private label product on super indo supermarket kelapa dua simultaneously or partially. The data used is primary data, collected through distributing questionnaires to 120 customers of Superindo Kelapa Dua’s customers buying private labels’ snacks. The method used in this study is a quantitive method and the results of the study are based on respondents’ answers using a Likert scale. Data analysis method used in this research are Multiple Linear Regression Test, F test, t Test, and Coefficient of Determine.Based on the result of this study Product Quality, Price, and Brand Image simultaneously have an effect on Purchase Interest, Product Quality has an effect on Purchase Interest, Price has no effect on Purchase Interest, and Brand Image has an effect on Purchase Interest.